Taxonomy, distribution and ecology of the order Phyllodocida (Annelida, Polychaeta) in deep-sea habitats around the Iberian margin - Ravara, Ascensão (2020)
The polychaetes of the order Phyllodocida (excluding Nereidiformia and Phyllodociformia incertae sedis) collected from deep-sea habitats of the Iberian margin (Bay of Biscay, Horseshoe continental rise, Gulf of Cadiz and Alboran Sea), and Atlantic seamounts (Gorringe Bank, Atlantis and Nameless) are reported herein. Thirty-six species belonging to seven families – Acoetidae, Pholoidae, Polynoidae, Sigalionidae, Glyceridae, Goniadidae and Phyllodocidae, were identified. Amended descriptions and/or new illustrations are given for the species Allmaniella setubalensis, Anotochaetonoe michelbhaudi, Lepidasthenia brunnea and Polynoe sp. Relevant taxonomical notes are provided for other seventeen species. Allmaniella setubalensis, Anotochaetonoe michelbhaudi, Harmothoe evei, Eumida longicirrata and Glycera noelae, previously known only from their type localities were found in different deep-water places of the studied areas and constitute new records for the Iberian margin. The geographic distributions and the bathymetric range of thirteen and fifteen species, respectively, are extended. The morphology-based biodiversity inventory was complemented with DNA sequences of the mitochondrial barcode region (COI barcodes) providing a molecular tag for future reference. Twenty new sequences were obtained for nine species in the families Acoetidae, Glyceridae and Polynoidae and for three lineages within the Phylodoce madeirensis complex (Phyllodocidae). A brief analysis of the newly obtained sequences and publicly available COI barcode data for the genera herein reported, highlighted several cases of unclear taxonomic assignments, which need further study.